The Combination Analysis Between Bacillus thuringiensis Sip1Ab Protein and Brush Border Membrane Vesicles in Midgut of Colaphellus bowringi Baly - Cao, Dengtian; Xiao, Changyixin; Fu, Qian; Liu, Xinbo; Liu, Rongmei; Li, Haitao; Gao, Jiguo (Frontiers in Microbiology, 2022)
The secretory insecticidal protein Sip1Ab and crystal protein Cry8Ca from Bacillus thuringiensis (Bt) are widely recognized for their coleopteran insecticidal activities. It is worthwhile to investigate the insecticidal mechanisms of these two proteins against Colaphellus bowringi Baly, which is a serious pest of cruciferous vegetables in China and other Asian countries. To that end, the genes encoding the Sip1Ab and Cry8Ca proteins were amplified from the strain QZL38 genome, then expressed in Escherichia coli, after which bioassays were conducted in C. bowringi larvae. After feeding these two proteins, the histopathological changes in the midguts of C. bowringi larvae were observed using transmission electron microscopy (TEM), and the Brush Border Membrane Vesicle (BBMV) was extracted for competition binding assays. TEM showed that ingestion of Sip1Ab caused a significant reduction in growth of the larvae, disruption of midgut microvilli, and expansion of intercellular spaces. Competition binding assays demonstrated that Sip1Ab bound to C. bowringi BBMV with a high binding affinity. However, a mixture of the two proteins in equal proportions showed no significant difference in insecticidal activity from that of Sip1Ab. These results could provide a molecular basis for the application of Sip1Ab in coleopteran insect control and contribute to the study of the Sip1Ab insecticidal mechanism as well.